2020
DOI: 10.3390/rs12081232
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multi-Source Data and Machine Learning Approaches to Predict Winter Wheat Yield in the Conterminous United States

Abstract: Winter wheat (Triticum aestivum L.) is one of the most important cereal crops, supplying essential food for the world population. Because the United States is a major producer and exporter of wheat to the world market, accurate and timely forecasting of wheat yield in the United States (U.S.) is fundamental to national crop management as well as global food security. Previous studies mainly have focused on developing empirical models using only satellite remote sensing images, while other yield determinants ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 68 publications
4
35
0
Order By: Relevance
“…They were second only to Ridge in tuber yield and tuber set prediction. Both RF and Adaboost are tree-based ensemble learning techniques, and they are widely used in the field of crop yield prediction [ 5 , 42 ]. However, in this study, they were found to be inferior to Ridge, PLSR, and SVR in dealing with a small sample size with high dimensional features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were second only to Ridge in tuber yield and tuber set prediction. Both RF and Adaboost are tree-based ensemble learning techniques, and they are widely used in the field of crop yield prediction [ 5 , 42 ]. However, in this study, they were found to be inferior to Ridge, PLSR, and SVR in dealing with a small sample size with high dimensional features.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the traditional yield assessment method, the advanced remote sensing technique is based on a non-destructive and efficient approach which has great potential for estimating the crop production and monitoring the growth status over the growing season. In the past few decades, satellite data have been broadly used in crop yield prediction with various spatial and spectral resolution [ 5 , 6 , 7 ], but their adoption in precision farming is hampered by the nonnegligible cloud contamination and the poor spatial resolution [ 8 ]. Recently, the development of sensors promoted the application of unmanned aerial vehicles (UAVs) in precision agriculture [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once again, R 2 was their metric of choice, and their success with similar models such as random forest helped motivate the current work to apply ML to a related problem [23]. Wang et al [9] used ML to predict yields for winter wheat in the CONUS in their 2020 paper, where they combined multiple sources of data including satellite imagery, climate data, and soil maps to train a support vector machine (SVM), AdaBoost model, deep neural network (DNN), and a random forest with positive results measured in R 2 and mean absolute error (MAE), such as the current work, as well as root mean squared error (RMSE) [9]. Our work adopted a simpler approach but used fewer varieties of data, all of which were publicly available, whereas ours did not require processing image data.…”
Section: Related Workmentioning
confidence: 96%
“…Our work extends and generalizes this approach by reporting R and R 2 , trying some different models, and using more accessible datasets with simpler features. Other previous work in this area generally used more complex data collection techniques, such as unmanned aerial vehicles (UAVs) [7], remote sensors [8], and satellite imagery [9]. Our primary contributions are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have also tackled the estimation of plant growth-related traits by data fusion from different sensors [11][12][13][14] for the computation of crop surface models based on image mosaicing methods [15][16][17][18]. Other approaches rely on the computation of individual aerial images.…”
Section: Introductionmentioning
confidence: 99%